Reverse Electron Transport at Mitochondrial Complex I in Ischemic Stroke, Aging, and Age-Related Diseases - Vishal Chavda; Bingwei Lu (MDPI AG, 2023)
Stroke is one of the leading causes of morbidity and mortality worldwide. A main cause of brain damage by stroke is ischemia-reperfusion (IR) injury due to the increased production of reactive oxygen species (ROS) and energy failure caused by changes in mitochondrial metabolism. Ischemia causes a build-up of succinate in tissues and changes in the mitochondrial NADH: ubiquinone oxidoreductase (complex I) activity that promote reverse electron transfer (RET), in which a portion of the electrons derived from succinate are redirected from ubiquinol along complex I to reach the NADH dehydrogenase module of complex I, where matrix NAD+ is converted to NADH and excessive ROS is produced. RET has been shown to play a role in macrophage activation in response to bacterial infection, electron transport chain reorganization in response to changes in the energy supply, and carotid body adaptation to changes in the oxygen levels. In addition to stroke, deregulated RET and RET-generated ROS (RET-ROS) have been implicated in tissue damage during organ transplantation, whereas an RET-induced NAD+/NADH ratio decrease has been implicated in aging, age-related neurodegeneration, and cancer. In this review, we provide a historical account of the roles of ROS and oxidative damage in the pathogenesis of ischemic stroke, summarize the latest developments in our understanding of RET biology and RET-associated pathological conditions, and discuss new ways to target ischemic stroke, cancer, aging, and age-related neurodegenerative diseases by modulating RET.